A fast calculation method for the optimal clearance and stiffness of the aerostatic guideway considering fluid-structure interaction. (May 2023) - Qi, Lizi; Zhu, Min; Gao, Qiang; Xu, Jingfeng; Liu, Liang; Wei, Wenyuan; Lu, Lihua
Abstract: The static performances of the aerostatic spindles/guideways are significantly affected by the fluid-structure interaction (FSI) effect. However, the existing two-way FSI calculation method for the aerostatic spindles and guideways is inefficient. It takes much time to calculate the optimal parameters and static performance in the design and study process. This paper proposes a fast calculation method for the optimal clearance and stiffness of the aerostatic guideway considering FSI, and the calculation process of a cruciform-layout aerostatic guideway was detailed as a case study. Moreover, the accuracy of the proposed fast calculation method is verified numerically and experimentally, which proves that the computational efficiency can be improved dozens or even hundreds of times under the premise of minor calculation errors.